A Tale of Three Cities: Deconstructing the Cross of Gastines in Paris, 1571 - Joashi, Tom; Sternberg, Maximilian (Artium Quaestiones, 2025)
This article considers the erection and subsequent removal of the Parisian Cross of Gastines, a monument commemorating the execution of three Protestant men, between 1569 and 1571. It seeks to foreground the spatial qualities of this tumultuous episode, with riots breaking out in December 1571, using the writing of Jacques Derrida on Bernard Tschumi’s project for the Parc de la Villette. The monument is read in this light as an inherently unstable semantic object, as opposed to the fixed edifice it was claimed to be upon its construction in 1569. In this way, the case is made for interpreting the Cross and the surrounding upheaval as an independently rich moment in Paris’ urban history, and not simply as a forewarning of the much-discussed St. Bartholomew’s Day Massacre of 1572. The article emphasises that Paris, in the midst of the French Wars of Religion (1562–1598), was a contested city: its late medieval image as a well-ordered bonne ville was challenged by the spread of both the learned, Humanist culture of the late Renaissance, which sought to classicize the city, and the militiant Catholicism of the Counter Reformation, which sought to cleanse it of religious heterodoxy. All three of these categories were the product of urban performance, enacted via theatrical statements of identity in the public arena. Employing Derrida’s description of a deconstructed architecture as one whose meaning is predicated on immediate, embodied interaction, it is shown how the Cross’ meaning was tied up with this performative theme. With the conclusion of France’s third civil war in 1570, the peace edict subsequently drawn up decreed that all markers of past conflict were to be removed, including the Cross of Gastines, although it was perhaps the triumphal entry of Charles IX down the Rue Saint-Denis in 1571, past Classical arches, obelisks, and other decorations, as well as the Cross itself, that truly spelt the monument’s symbolic end. Further performances followed: when, after much back and forth, the city administration finally obeyed the king’s orders and initiated its removal to the Cemetery of the Innocents, the Catholic mob took to the streets to demonstrate that their faith was not so easily dismantled. Officials mobilised in response, enacting their own image of the city as one of control and order. As Derrida writes of the folies of La Villette, it was thus via that the many movements around the Cross that its various meanings were revealed.